PENGARUH CITRA PERUSAHAAN DAN KEPERCAYAAN NASABAH TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA NASABAH BCA KCP NGALIYAN) (Students' Journal of Economic and Management, 2016)
The development ofthe bankingsectorhas ledto intense competition. Competitionrequires eachbankvying toprovide the best serviceto thecustomers, both inthe quality oftheservice-oriented customer satisfaction orcustomer(customer satisfaction) as well as the quantityis toincrease the typesof productsthat are consideredto beinthe desireof its customers.The analysis toolusedis multiple linear regression The results showed thatthe influence ofimageand truston customer loyaltyand satisfactionasan intervening variable(customer case study atBCAKCPNgaliyan) Keywords: corporate image, customer trust, customer statisfaction and customer loyalty